(untitled) (Research, Society and Development, 2020)
The use of medicinal plants is an alternative for the treatment and prevention of diseases that affect animals, since it is a low cost method and easily acquired by the producer. Thus, the objective of this study was to evaluate the population knowledge in the Paraiban semi-arid region regarding the use of plants with healing properties for animals. The research was conducted in the 14th Administrative Region of Paraíba Technical Assistance and Rural Extension Company, based in Pombal-PB, promoting a descriptive field research with a qualitative approach. As an instrument for data collection, a previously structured questionnaire containing objective and subjective questions was used. It was observed that among the respondents that the most used medicinal plant to cure animal diseases was lemon (Citrus limonum) with 12.14%, followed by Fedegoso (Senna occidentalis) with 10.57%, wild bean (Capparis flexuosa) equivalent to 9.57% and therefore aloe vera (Aloe vera) with 8.14%. Among the families that stood out the most are Anacardiaceae, Fabaceae and Euphorbiaceae, both with endemic Caatinga species.